The Real Exchange Rate and Export Growth : Are Services Different? - Eichengreen, Barry (World Bank, Washington, DC, 2014)
This paper considers the determinants of exports of modern services and traditional services. It considers the growth of export volumes as well as export surges, that is, the periods of rapid sustained export growth. It asks whether the determinants of export growth rates and export surges differ between merchandise, traditional services, and modern services and whether developing countries are different. It confirm the importance of the real exchange rate for export growth. The paper finds that the effect of the real exchange rate is even stronger for exports of services than for exports of goods and that it is especially strong for exports of modern services. The results suggest that in the course of their development, as developing countries shift from exporting commodities and merchandise to exporting traditional and modern services, appropriate policies toward the real exchange rate become even more important.